Research on Meshing Stiffness and Bearing Performance of Logarithmic Modified Composite Roller Movable Tooth - Yali Yi; Lei He; Liang Xie; Shuang Zhang; Herong Jin; Zhengxiang Zhou; Yazheng Zhou (Jixie chuandong)
Aiming at the development requirements of large load capacity and long life of wheel-side deceleration system， a logarithmic modified composite roller movable tooth transmission is proposed. Combined with the current research on the contact deformation of hollow roller， a method for calculating the meshing deformation of logarithmic modified composite roller is proposed by introducing design parameters Δc and Δe. The influence of filling degree and different rollers on meshing stiffness is analyzed. The finite element method is used to compare and analyze the equivalent stress distribution of different rollers. The results show that under the same load conditions， the meshing stiffness of the logarithmic modified composite roller movable tooth is slightly higher than that of the hollow roller， and the meshing stiffness decreases with the increase of the filling degree. The logarithmic modified composite roller can effectively improve the edge stress concentration and reduce the maximum equivalent stress.